Addressing the Practice of Religious Tolerance by Panji Gumilang (In the studies of Wahbah Az-Zuhaili and Quraish Shihab) - Mualik Fauzi; Rifqatul Husna (LP. Ma'arif Janggan Magetan, 2024)
Studying the subject of religious tolerance is always fascinating. This research holds a significant place in the field of religion studies because to the fluctuations in relationships between religious groups throughout different regions of the world, including Indonesia. Numerous Islamic scholars, particularly those who study tafsir, attempt to define tolerance normatively by drawing on passages from the Quran. Wahbah al-Zuhayli is a modern scholar who takes tolerance very seriously. Al-Zuhayli's interpretation, while methodologically sound, generally adopts the methodology of ancient ulama literature. But the issue of tolerance that he highlights stems from the social reality that religious communities currently inhabit. Al-Zuhayli opens his discussion on tolerance by elucidating the notion of wasatiyyah al-Islam, or Islamic moderation. Al-Zuhayli then categorized the four primary themes of tolerance found in the Koran. First, the interactions amongst the Samawi faiths. Forming a moderate and tolerant mindset is made possible by the heavenly religion's shared core doctrines. The second is the freedom to select one's religion. This point demonstrates how Islamic law upholds the Ri'ayah al-Din concept. The third is the ban on inciting hate. Fourth, the advice to put justice first and the outlawing of acts of terror. Each and every person is entitled to protection for their soul's freedom. According to Al-Zuhayli's perspective, religious groups generally get along well and are tolerant of one another. This is also a scientific refutation of the violent ideologies that radical organizations frequently advance.